'I understood the words but I didn't know what they meant': Japanese online MBA students' experiences of British assessment practices. (3rd May 2016) - Fenton-O'Creevy, Mark; van Mourik, Carien
Abstract: We report on a case study of high Japanese student failure rates in an online MBA programme. Drawing on interviews, and reviews of exam and assignment scripts we frame the problems faced by these students in terms of a 'language as social practice' approach and highlight the students' failure to understand the specific language games that underpin the course assessment approach. We note the way in which the distance learning and online context can make the challenges faced by international students less immediately visible to both students and institution.